The Making of the Artefacts and Architectural Remains as Props for the Performance of "Bermulanya Di Sini.... Kedah Tua" - Mohd Najib Abdullah Sani,; Muhizam Mustafa, (Wacana Seni Journal of Arts Discourse, 2019)
"Bermulanya Di Sini...Kedah Tua" demonstrates a historical data interpretation of the Kedah Tua early society at Sungai Batu within the artistic context of stage performance demonstrating series of dance and stage act. The purpose of this paper is to elucidate the props making process for the stage performance from a designer-maker point of view, by demonstrating the philosophy of body movements and the connection to object designs in space. Furthermore, the props making encompasses the imitation and construction of two scaled building artefacts which are the ancient iron smelting furnace and the circular ritual monument that significantly embodies the early civilisation of Kedah Tua society between the 2nd and 6th CE. The research-design team has successfully constructed the ancient buildings' props using wire structured paper maché technique and Styrofoam sheets assembling in various scaled sizes. In order to accommodate the performance need on the stage, the modular concept have been introduced in the design of the props by embedding the elements of object's practicality, portability and, easy assembling and disassembling.